2018
DOI: 10.7554/elife.41305
|View full text |Cite
|
Sign up to set email alerts
|

Targeted degradation of BRD9 reverses oncogenic gene expression in synovial sarcoma

Abstract: Synovial sarcoma tumours contain a characteristic fusion protein, SS18-SSX, which drives disease development. Targeting oncogenic fusion proteins presents an attractive therapeutic opportunity. However, SS18-SSX has proven intractable for therapeutic intervention. Using a domain-focused CRISPR screen we identified the bromodomain of BRD9 as a critical functional dependency in synovial sarcoma. BRD9 is a component of SS18-SSX containing BAF complexes in synovial sarcoma cells; and integration of BRD9 into these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
170
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(176 citation statements)
references
References 54 publications
6
170
0
Order By: Relevance
“…Their rarity and recent discovery currently precludes any definitive statement regarding their susceptibility to specific therapeutic regimens. A recent report has demonstrated the susceptibility of synovial sarcoma cells harboring a SS18‐SSX fusion to a small molecule degrader of the NUTM1 fusion partner BRD9 . BRD9 is a crucial component of the oncogenic SWI\SNF (BAF) chromatin remodeling complex and its degradation induces downregulation of oncogenic transcriptional programs and inhibits tumor progression in vivo.…”
Section: Diagnostic and Therapeutic Implicationsmentioning
confidence: 99%
“…Their rarity and recent discovery currently precludes any definitive statement regarding their susceptibility to specific therapeutic regimens. A recent report has demonstrated the susceptibility of synovial sarcoma cells harboring a SS18‐SSX fusion to a small molecule degrader of the NUTM1 fusion partner BRD9 . BRD9 is a crucial component of the oncogenic SWI\SNF (BAF) chromatin remodeling complex and its degradation induces downregulation of oncogenic transcriptional programs and inhibits tumor progression in vivo.…”
Section: Diagnostic and Therapeutic Implicationsmentioning
confidence: 99%
“…We have previously demonstrated that prior to the application of drug, there is a rare subpopulation of cells (pre-resistant cells) that express high levels of a number of markers, and that these "primed" cells are far more likely to become resistant than other cells 14 . In order to identify modulators of the fluctuations that lead to the formation of this subpopulation of primed cells, we designed a large scale loss-of-function pooled CRISPR genetic screen (which we dubbed the "priming screen") comprised of ~13,000 single guide RNAs (sgRNAs) targeting functionally relevant domains of ~2,000 proteins, with roughly six distinct single guide RNAs per domain (1402 transcription factor targets, 481 kinase targets, 176 epigenetic targets; each single guide RNA targets an important functional domain, see Supplemental Tables 1-3) [27][28][29] .…”
Section: Crispr/cas9 Genetic Screens Identify Factors That Affect Primentioning
confidence: 99%
“…Approximately 6 independent single guide RNAs were designed against individual DNA binding domains (Supplementary tables 1-3). [27][28][29] The design principle of single guide RNA was based on previous reports and the single guide RNAs with the predicted high off-target effect were excluded (Hsu et al 2013) . For the initial pooled CRISPR screens, all of the single guide RNAs oligos including positive and negative control single guide RNAs were synthesized in a pooled format (Twist Bioscience) and then amplified by PCR.…”
Section: Construction Of Domain-focused Single Guide Rna Pooled Librarymentioning
confidence: 99%
“…This suggests that the BAF complex containing the SS18‐SSX fusion protein is deficient in SMARCB1 function. SMARCB1‐deficient cancer cells and SS18‐SSX fusion cancer cells are synthetic lethal because of inhibition of a subunit of the ncBAF complex, such as BRD9 . Thus, BAF complex‐deficient cancers, such as SMARCB1‐deficient cancers, depend on the function of the residual ncBAF complex.…”
Section: Synthetic Lethal Targets Based On Targeting the Interaction mentioning
confidence: 99%
“…are synthetic lethal because of inhibition of a subunit of the ncBAF complex, such as BRD9. 18,29,30 Thus, BAF complex-deficient cancers, such as SMARCB1-deficient cancers, depend on the function of the residual ncBAF complex. A BRD9 inhibitor would therefore be a promising strategy for SMARCB1-deficient cancers.…”
Section: Smarcb1-deficient Cancer Cells and Ss18-ssx Fusion Cancer Cellsmentioning
confidence: 99%